Does aid for trade contribute to M&A FDI flows to developing countries? - Ly-My, Dung (2022)
Since the Aid for Trade (AfT) Initiative was launched in 2005, there have been many studies investigating the effects of AfT on trade and foreign direct investment (FDI). Most studies have found positive effects of AfT on exports and imports of recipient countries, as well as on aggregate FDI flows to recipient countries. Lee and Ries (World Dev 84: 206–218, 2016) and Ly-My and Lee (World Econ 42: 2120–2143, 2019) found positive effects of AfT particularly on greenfield FDI to recipient countries. Noting that there are two entry modes of FDI (greenfield and M&A), this study fills a gap in the literature by investigating the effects of AfT on cross-border M&A flows to recipient countries. By using the system GMM estimator with a dataset of 102 countries for 2003–2016, this paper finds evidence that AfT has a positive and significant effect on the US dollar value of M&A investment flows to recipient countries. Specifically, we find that AfT results in an increase in the dollar value of M&A FDI inflows because it increases both the extensive and intensive margins of M&A deals as well as source countries. Our results add to the beneficial effects of AfT on the recipient countries, as there is ample evidence of the benefits of M&A FDI.